PENGARUH BENTUK KRIB TIPE TIANG TERHADAP POLA ALIRAN - Ahmad Syarif Sukri; Riswal Riswal K. (STABILITA || Jurnal Ilmiah Teknik Sipil, 2018)
The Impact of Post Crib types on the flow pattern, This laboratory research was conducted at the meander shape canal flowing furrow. The research objective to study the cribs type Post to the flow pattern,and flow rate as the results of crib setting with hydraulic parameter interaction ( velocity, depth,and discharge ),and the interaction of Post cribs. The length variation of the research segments namely segment I 50o (s)=0,785 m, and segment II 90o (s)=1.884 m. the discharge was determinet at the depth of Thomson gate with interval Q1=0,00601435 m3/second, Q2=0,00748878 m3/second, Q3=0,00896734 m3/second, and Q4=0,01044860 m3/second; whereas, the measurement of velocity was done by Current Meter.The results of the flow transformation study indicate that before the instalation of cribs, the flow velocity is outside the segment of the Q1, Q2, Q3and Q4 discharge. After the installation of crib types Post, the change of flow pattern is towerd the middle of the segment on the Q1, Q2, Q3 and Q4 flow. The change of the velocity flow outside, inside, and in the middle of the segment occurs at the placement of ackmon crib type; therefore, the size of wet section on each side changes accordingly.